Subsequent perinatal outcomes of pregnancy with two consecutive pregnancies with gestational diabetes mellitus: A population‐based cohort study. Issue 4 (3rd April 2022) - Guo, Yanni; Xu, Xia; Xu, Weijiao; Liao, Tingting; Liang, Jie; Yan, Jianying
Abstract: Background: Gestational diabetes mellitus (GDM) is glucose intolerance diagnosed during pregnancy. We aimed to explore the different outcomes of women with two consecutive pregnancies with GDM. Methods: This study included 861 women with recurrent GDM who had two consecutive singleton deliveries at Fujian Maternity and Child Health Hospital between May 2012 and September 2020. Data on pregnancy complications and neonatal and delivery outcomes were collected and analyzed. Results: Among those women with recurrent GDM, there was no difference in pregnancy complications in index pregnancy vs subsequent pregnancy. Our data revealed there was a significantly higher incidence of thyroid disease in the subsequent pregnancies than in the index pregnancy. (6% vs 10%, p = .003)In subsequent pregnancies, the birth weight was greater than that of the index pregnancy (3296.63 ± 16.85 vs 3348.99 ± 16.05, p = .025); and the incidence of large for gestational age (LGA) was higher than that of the index pregnancy (16.3% vs 20.6%, p = .021). More cesarean sections occurred in the subsequent pregnancy. (32.9% vs 6.6%, p = .039). Postpartum hemorrhage, premature birth, and placental abruption were not significantly different between the two pregnancies. Conclusions: The results suggest the effect of GDM on thyroid dysfunction may be persistent. Recurrent gestational diabetes results in a higher rate of cesarean delivery, incidence of LGA, and neonatal admission to the neonatal intensive care unit (NICU) in subsequent pregnancies. We need to pay attention to the postpartum thyroid function of pregnant women with GDM. Further studies are still needed on recurrent GDM to reduce this occurrence of admission to NICU. Abstract : Highlights To summarize, we found that the incidence of complications in subsequent pregnancies in women with recurrent GDM did not differ from that in their index pregnancies. There is a high incidence of thyroid disease in women with recurrent GDM in this study. And whether thyroid disorders increase in women with a history of GDM needs to be confirmed by further studies. The main reasons for cesarean delivery in women with uncomplicated GDM were fetal distress, macrosomia, and failed induction of labor. Therefore, prenatal guidance and the pre‐delivery evaluation of women with their first incidence of GDM are especially important and need careful clinical management. There is a high rate of neonatal admission to NICU in cases of recurrent GDM, mainly due to neonatal respiratory disease. This study had some limitations. Firstly, our study is a single‐center observational cohort study with a moderate sample size and no control group. Secondly, these changes can not be ruled out due to the possibility of age. Further research is required to investigate how we can reduce this occurrence. 摘要: 背景: 妊娠期糖尿病(GDM)是妊娠期确诊的糖耐量异常。我们的目的是探索连续两次妊娠的GDM妇女的不同结局。 方法: 研究对象为自2012年5月至2020年9月在福建省妇幼保健院连续两次单胎分娩的复发性GDM患者861例。收集并分析妊娠并发症, 新生儿和分娩结局。 结果: 在复发性GDM患者中, 首次妊娠与再次妊娠在妊娠并发症方面无明显差异。我们的数据显示, 再次妊娠时甲状腺疾病的发病率明显高于首次妊娠(6% vs 10%, p=0.003)。再次妊娠组新生儿出生体重高于首次组(3296.63±16.85g vs 3348.99±16.05g, p=0.025), 大于胎龄儿(LGA)高于首次组(16.3% vs 20.6%, p=0.021)。再次妊娠时发生更多的剖腹产(32.9% vs 6.6%, P=0.039)。两组在产后出血, 早产, 胎盘早剥的差异无统计学意义。 结论: 本研究结果提示GDM对甲状腺功能障碍的影响可能是持久的。复发的妊娠期糖尿病具有较高的剖宫产率, LGA发生率, 以及更多的进入新生儿重症监护病房(NICU)的新生儿。GDM孕妇的产后甲状腺功能有待进一步研究, 以降低NICU的发生率。